1998
DOI: 10.1046/j.1365-3091.1998.00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and mechanical processes during burial diagenesis of chalk: an interpretation based on specific surface data of deep‐sea sediments

Abstract: Burial diagenesis of chalk is a combination of mechanical compaction and chemical recrystallization as well as cementation. We have predicted the characteristic trends in specific surface resulting from these processes. The specific surface is normally measured by nitrogen adsorption but is here measured by image analysis of scanning electron micrographs. This method concentrates on the micritic matrix alone. Deep‐sea sediments are ideally suited to the study of burial diagenesis because they accumulate in a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 22 publications
1
48
0
Order By: Relevance
“…Image analysis was done on backscatter electron micrographs of impregnated polished samples also studied by Borre & Fabricius (1998), to measure nannofossil matrix porosity, and amounts of large particles (e.g. foraminifers) and pores by use of the filtering method described by Borre (1997;Figs 2 and 3).…”
Section: Ontong Java Plateaumentioning
confidence: 99%
See 1 more Smart Citation
“…Image analysis was done on backscatter electron micrographs of impregnated polished samples also studied by Borre & Fabricius (1998), to measure nannofossil matrix porosity, and amounts of large particles (e.g. foraminifers) and pores by use of the filtering method described by Borre (1997;Figs 2 and 3).…”
Section: Ontong Java Plateaumentioning
confidence: 99%
“…Recrystallization involves local simultaneous dissolution of carbonate particles and overgrowth on carbonate particles, where no net transport of Ca 2+ and CO 2À 3 is required and no porosity change necessarily is involved, whereas pore-filling cementation is a result of diffusion and net precipitation of material derived, e.g. from dissolution at stylolites (Borre & Fabricius, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This study uses the term deep burial diagenetic realm when burial depths were sufficient for the onset of chemical compaction as a result of increasing overburden pressure. For carbonate deposits this typically requires a few 100 m of burial (e.g., Hood & Nelson 1996;Nicolaides & Wallace 1997;Borre & Fabricius 1998). By this stage, pore fluid chemistry is usually influenced by increased temperatures and pressures, and possibly salinities, in a strongly reducing environment, involving marine-modified or connate fluids.…”
Section: Diagenetic Environments Dennedmentioning
confidence: 99%
“…This depth interval is commonly referred to as the ooze interval [16]. In this interval, mechanical compaction forms a more rigid rock frame [17] and we may have contact cementation [6].…”
Section: Chalk Deposition and Diagenesismentioning
confidence: 99%
“…This progressive diagenesis (ooze-chalk-limestone) has been addressed by many authors and includes changes in the pore geometry [10,19] as well as the reduction in porosity (e.g. [2,16,17,20,21]). Saberi et al [10] showed how we can incorporate the effect of these changes into rock physics characterization of the chalks (Fig.…”
Section: Chalk Deposition and Diagenesismentioning
confidence: 99%